Peran Ikatan Mahasiswa Muhammadiyah (IMM) Sebagai Gerakan Dakwah Di Lingkungan Kampus Universitas Islam Ahmad Dahlan Kabupaten Sinjai - Suriyati, Suriyati; Suriati, Suriati; Rahmatullah, Rahmatullah; Fatimahtu Sahra, Siti; Ramadhan , Fauzan (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2024)
The Muhammadiyah Student Association (IMM) in the Da'wah Movement at the Ahmad Dahlan Islamic University (UIAD) Campus intends to strengthen Faith and Piety, especially in activities that are often carried out. This research is a descriptive qualitative study. The data collection techniques are observation, interviews and documentation. The subjects in this study were IMM cadres and UIAD students. The results of the study found that the role of IMM in da'wah has been realized but the involvement of participants is very minimal. In Da'wah, many methods or ways are found such as oral or direct methods, writing, actions or policies. The da'wah movement is based on QS Ali-Imran / 3: 104 which explains that a group of people are called to do good, inviting them to good deeds and preventing them from evil deeds. In da'wah there are supporting and inhibiting factors in the realization of an activity. An example of a supporting factor is the desire in the heart to believe in Allah SWT in this case implemented by participating in activities. Meanwhile, the inhibiting factor itself is the lack of communication and participation from the surrounding environment.